Pengaruh Selebrity Endorsme, Brand Image, dan Testimoni dalam Meningkatkan Minat Beli Produk (Studi Kasus : Instagram UKM Kylafood) - Ogi Maulana Firli; Muhamad Rizal; Ria Arifianti; Asmaul Husna (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
The purpose of this study is to determine the effect of Celebrity Endorsement, Brand Image, and Testimonials on consumer buying interest in Kylafood products on Instagram Social Media. The research methods used in this research are descriptive and quantitative methods. Data analysis techniques and research model submissions use Structural Equation Modeling-Partial Least Square (SEM-PLS) with 95 questionnaire distribution data aimed at people who at least follow one celebrity endorsment on Instagram, know the kylafood brand, know the testimonials of the kylafood brand and intending to buy kylafood products. The results of this study state that the celebrity endorsement and testimonial variables have a significant positive effect on buying interest in Kylafood products on Instagram, while the brand image variable has a positive but not significant effect.